EFEK PAPARAN KRONIS PESTISIDA TERHADAP KADAR ASPARTAT AMINOTRANSFERASE (AST) DAN ALANIN AMINOTRANSFERASE (ALT) PADA SUBYEK PETANI - Devyana Dyah Wulandari; Andreas Putro Ragil Santoso; Devyani Diah Wulansari (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
Farmers in Indonesia are very dependent on pesticides to protect their crops from pests. Farmers are one of the subjects who are susceptible to pesticides and can cause disease due to pesticide accumulation. One of the disease that can arise due to exposure to pesticides is liver damage. This study wanted to determine the effect of pesticide exposure on liver damage seen from AST and ALT enzyme levels using farmer respondents in the Mojokerto area of 25 respondents. From the results of the study it was found that AST levels were influenced by age (P = 0.017), length of work (P = 0.035), and PPE usage (P = 0.044), while age, work period, length of work and usage of PPE did not significantly influence to ALT levels. It can be concluded that age, length of work and use of PPE affect AST levels. Therefore, to prevent the occurrence of pesticide poisoning, farmers must obey the rules on the use of pesticides such as using PPE regularly and always consuming healthy food.